Efforts of the Head of Madrasah MIS Raudlatul Atfal 3 in Improving Student Reading Literacy Based on AKMI Results in 2023 - Anwar, Ach.; Hidayatillah, Yetti; Ikmal, Moh. (SAINTIS Publishing, 2024)
This study explores the efforts of the principal of MIS Raudlatul Athfal 3 to enhance students' competencies based on the 2023 Indonesian Madrasah Competency Assessment (AKMI) results. The AKMI outcomes revealed varied student achievements, with most categorized as